FAMILY PROJECTIONS AFTER COVID-19: A TURNING POINT? - Fahri Çakı (İmgelem)
The global experiences of Covid-19 (such as staying at home, physical distance and social isolation practices, moving work and education to home, unemployment, income losses, digitalization) gave birth to the idea of a "new normal" and to projections predicting that it would fundamentally affect the future of family structure along with other areas of life. Critically examining the literature in terms of the effects of Covid-19 specifically on the family and the projections related to it, this paper argues that a new discourse centered on Covid-19 has been produced, which presents it as a 'turning point' as if it had revolutionary effects in human history. Based on the aim of making a critical evaluation of this discourse, firstly, some basic features of future projections were determined. Secondly, the risk/uncertainty/fear environment emphasized by the discourse in question is discussed within the framework of the relevant literature. Third, projections for the future of family life are examined and discussed within the framework of three main themes. This paper shows that, contrary to the emerging new discourse, family transformations and discussions related to Covis-19 were already happening in many societies long before Covid-19. Therefore, it is concluded that the new discourse uses Covid-19 as a scapegoat for the problems of the reconstructed order of global capitalism, which deepens inequalities and ignores disaster preparedness.